Characterization of amylose nanoparticles prepared via nanoprecipitation: Influence of chain length distribution. (15th August 2018) - Chang, Yanjiao; Yang, Jingde; Ren, Lili; Zhou, Jiang
Highlights: Amylose pastes were treated with β-amylase for different periods of time. Chain length of amylose was tailored through the β-amylase treatment. Amylose nanoparticles (ANPs) were prepared through nanoprecipitation. Chain length of amylose was a critical factor to influence size of ANPs. The β-amylase treatment gave the ANPs smaller size and narrower size distribution. Abstract: The influence of chain length distribution of amylose on size and structure of the amylose nanoparticles (ANPs) prepared through nanoprecipitation was investigated. Amylose with different chain length distributions was obtained by β-amylase treating amylose paste for different times and measured by size exclusion chromatography (SEC) and fluorophore-assisted carbohydrate electrophoresis (FACE). ANPs prepared via precipitation were characterized by using dynamic light scattering (DLS), scanning electron microscopy (SEM) and X-ray diffraction (XRD). Results showed that the β-amylase treatments led to decrease in chain length of amylose, and it was the most important factor affecting size of ANPs. When hydrolysis degree of amylose was 52.8%, mean size of ANPs decreased from 206.4 nm to 102.7 nm. All the ANPs displayed a V-type crystalline structure and the effect of amylose chain length on crystallinity of the precipitated ANPs was negligible in the investigated range.